KOMPETENSI SOSIAL GURU DALAM PERSPEKTIF HADITS - Yus, Sulhan; Mariati; Ariani, Safrina (LPPM STAI Muhammadiyah Probolinggo, 2025)
Social competence is the ability of a teacher who is able to interact with people around him, both with fellow teachers, students, education personnel and also the surrounding community. Social competence is often not considered important by teachers because it is not directly related to the implementation of learning, so there are teachers who show less mastery of social competence. The purpose of this study is to explore the hadiths of the Prophet that intersect with the social competence of teachers. The research method used in this research is a qualitative approach library research model. Data collection through collecting various kinds of literature such as hadith books, articles, and books. The results showed that there are several hadiths that contain social competencies that must be possessed by all teachers, in order to become an ideal teacher for himself, his students, student guardians and also the surrounding community. Like the hadith narrated by Bukhari where, teachers who are patient with the disturbances they receive from social interactions, are better than teachers who avoid associating with their social environment. Then the hadith narrated by Ad-darimi which emphasizes the importance of teachers not looking down on others and not utilizing their knowledge only for the benefits of the world. Given that one of the requirements for being a professional teacher is to have social competence, it is fitting that every teacher master social competence in order to be able to become a professional teacher.